Kajian Antropolinguistik: Makna Simbolik Bolanafo Secara Religi Pada Pernikahan Adat Suku Nias - Telaumbanua, Agus Arda Setiawan; Lubis, Dalmidah; Harefa, Yakobus Nosiduhu (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This paper discusses the Bolanafo of marriage in Nias society. The focus of discussion in this paper is how important Bolanafo is as a factor in the traditional marriage of the Nias tribe and how Christianity theologically views Bolanafo. To fulfill the research objectives, a number of literature studies were conducted by utilizing literature and conducting interviews related to Bolanafo in the Nias marriage system. All the literature data was processed and analyzed, as a research conducted by literature study, the results of this research are presented descriptively. The culture in Nias marriage is still very strong and is practiced until today. It must be realized that serving bolanafo in a Nias wedding is not something that is outdated or involves a complicated process. Doing so is an effort to maintain identity as Ono Niha wherever they are.